Potensi Wisata Bukit Lawang Sebagai Kawasan Unggulan Ekowisata - Sianipar, Christina Indriani; Riyanti, Imelda Vega (Politeknik Pariwisata Medan, 2024)
Tourism potential of Bukit Lawang for ecotourism superior area. Bukit lawang is one of the potential tourist attractions in Gunung Leuser National Park. Bukit lawang is located in the utilization zone of Gunung Leuser National Park. Orangutan is one of the two species of Orangutan in Indonesia and can only be found on the island of Sumatra. This place also has tourism potential with fast and clear river currents. Research is conducted to describe a symptom, event, and incident that occurs factually, systematically and accurately. In general, research methods have 3 types, namely quantitative, qualitative and mixed. In this study the authors used qualitative research methods by means of interviews and used SWOT + Matrix analysis. SWOT analysis is used to analyze internal factors and external factors which will then become strategic actions and profitable business optimization Bukit Lawang tourist attraction has been known both domestically and abroad. Bukit lawang has developed into a popular ecotourism center in North Sumatra. Many tourists come to participate in jungle trekking, watch orangutans in the wild, and enjoy the beautiful nature. One of the most famous activities in Bukit Lawang is forest trekking to see orangutans. Bukit lawang also offers other nature tourism activities such as river tubing, rafting and walking. Bukit lawang is a destination located in North Sumatra, Indonesia that is famous for its natural beauty, especially as the home of the lying orangutan. However, like other tourist attractions, Bukit Lawang has a number of advantages and disadvantages. The pros of bukit lawang include spectacular natural scenery, the opportunity to see wild orangutans in their natural habitat and a variety of outdoor activities such as hiking and tubing. On the other hand, the lack of government contribution in utilizing the untapped tourism potential and the lack of public awareness of tourism awareness.